2016
DOI: 10.5498/wjp.v6.i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in caregiving among family - caregivers of people with mental illnesses

Abstract: All over the world women are the predominant providers of informal care for family members with chronic medical conditions or disabilities, including the elderly and adults with mental illnesses. It has been suggested that there are several societal and cultural demands on women to adopt the role of a family-caregiver. Stress-coping theories propose that women are more likely to be exposed to caregiving stressors, and are likely to perceive, report and cope with these stressors differently from men. Many studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
422
7
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(489 citation statements)
references
References 110 publications
41
422
7
19
Order By: Relevance
“…Most of the caregivers that participated in the study were female, in coherence with the results of previous works [35] and with the fact that the care of the relatives used to rely on the female individuals of the family [2, 36]. The high percentage of actively working caregivers (62.3%) points to the fact that many of them are juggling their working and caring duties.…”
Section: Discussionsupporting
confidence: 82%
“…Most of the caregivers that participated in the study were female, in coherence with the results of previous works [35] and with the fact that the care of the relatives used to rely on the female individuals of the family [2, 36]. The high percentage of actively working caregivers (62.3%) points to the fact that many of them are juggling their working and caring duties.…”
Section: Discussionsupporting
confidence: 82%
“…Gender of the caregiver is one such factor that has been extensively studied with majority of studies showing female caregivers more likely to experience stress. 9,16 Study conducted in India, Pakistan and Sri Lanka, however found that gender was not a significant factor contributing to stress.…”
Section: Discussionmentioning
confidence: 95%
“…We found female spouses experienced more caregiver burden than male spouses, which is consistent with previous studies (Kim, Chang, Rose, & Kim, 2012; Penning & Wu, 2015). This may be explained by the fact that women in general tend to do more house chores, take care of dependents, and sometimes be the sole breadwinner for the family (Sharma, Chakrabarti, & Grover, 2016). This is especially true in Chinese culture where women often burden more work and shoulder the duty to support her family (Lai, Luk, & Andruske, 2007).…”
Section: Discussionmentioning
confidence: 99%